Self‐assembling cyclic peptide‐oligonucleotide conjugates: Synthetic strategies and the effect of cyclic topology on self‐assembly and base pairing. Issue 2 (23rd September 2020) - Kye, Mahnseok; Zhang, Zhihao; Lim, Yong‐beom
Abstract: Molecules often take advantage of cyclic topology to enable enhancement of their properties such as thermal stability, binding affinity to targets, and self‐assembly profiles. Despite the advantages of cyclization, peptide‐oligonucleotide conjugates (POCs) have not fully utilized the cyclic topology, presumably due to a dearth of generalized synthetic methods. Here, we report a feasible way to synthesize self‐assembling cyclic POCs using a thiol‐maleimide reaction and copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) in the solution phase and evaluate the properties of cyclic POCs such as molecular conformation, Watson‐Crick base pairing, and self‐assembly profile in comparison to those of linear POCs. Although there is a marginal difference between cyclic POCs and linear POCs in terms of their overall conformation, the self‐assembly profile is greatly affected. The cyclic POCs form homogeneous spherical aggregates, while the linear POCs form a heterogeneous population of fibrous and spherical aggregates. On the other hand, these cyclic POCs show less efficiency in Watson‐Crick base pairing to complementary cyclic POCs than linear POCs, which subsequently affects the self‐assembly of each duplex POC. Our study provides a synthetic method for self‐assembling cyclic POCs as well as a better understanding of the effect of cyclic topology on the overall conformation, self‐assembly, and Watson‐Crick base pairing of POCs. Abstract :